Analisis Kesesuaian Lahan Tanaman Padi di Kecamatan Gunung Talang Kabupaten Solok - -, Sholeha - (JURNAL BUANA, 2026)
This study aims to analyze the level of land suitability and improvement efforts needed for rice cultivation in Gunung Talang Sub-district, Solok District, which is one of the main rice producers in West Sumatra. The weighted product method was used to evaluate land suitability based on the factors of drainage, soil texture, cation exchange capacity (CEC), soil pH, slope, rainfall, and flood risk. The results showed that land in the study area was divided into four suitability classes: highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and unsuitable (N). Land 1 (362.41 ha) is categorized as S1, land 2 (939.68 ha) as S2, while land 3, 4, and 5 are categorized as S3. Land 6 and 7 are categorized as N. This research provides important information for optimizing the utilization of rice farming land in Gunung Talang, which has the potential to increase production and support regional food security.